Studies Towards the Synthesis and Characterization of Diphenyl Amine and Its Interaction with Various Metal Ions - Kaur, Nirmaljeet (My University, 2012)
Di-phenyl amines are useful organic compounds that are used as intermediates for manufacturing dyes, agro-chemicals and the pharmaceutical products. Present study was taken up to synthesized and analyzed using NMR of N-[2-(2-nitro-phenylamino)-phenyl]-acetamide,a diphenylamine.UV-Vis spectroscopic studies was carried out for the above compound and its intermediates in the presence of different metal ions viz. Zinc,Copper,Nickel,Cadmium,Mercury,Cobalt and Iron.No change in the UV-Vis absorption spectra was observed except in case of N-(2-Amino-phenyl)-acetamide,one of the intermediates,with Ferric salt and a blue shift was observed.Detailed studies with varying concentration of ferric ion were carried out.
Keywords: Aryl Amines, Anti-Oxidants; Buchwald-Hartwig Synthesis